2010
DOI: 10.1095/biolreprod.109.077495
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Ovarian Aging in the Absence of the Transcription Regulator TAF4B in Mice1

Abstract: The mammalian ovary is unique in that its reproductive life span is limited by oocyte quantity and quality. Oocytes are recruited from a finite pool of primordial follicles that are usually exhausted from the ovary during midadult life. If regulation of this pool is perturbed, the reproductive capacity of the ovary is compromised. TAF4B is a gonad-enriched subunit of the TFIID complex required for female fertility in mice. Previous characterization of TAF4B-deficient ovaries revealed several reproductive defic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 55 publications
0
39
0
Order By: Relevance
“…One of the best-characterized selective subunits of the general transcriptional complex TFIID is TBP-associated factor 4b (TAF4b), a paralog of TAF4, originally identified in a human B-cell line and found to be primarily enriched in the mouse ovary and testis (Freiman et al, 2001). Taf4b-deficient female mice are viable but infertile and suffer from many hallmarks of premature ovarian failure, including follicle depletion, persistent estrous and high serum levels of the gonadotropin follicle stimulating hormone (FSH) (Falender et al, 2005;Freiman et al, 2001;Lovasco et al, 2010;Voronina et al, 2007). Recent work has demonstrated that Taf4b-deficient ovaries experience dramatic germ cell loss by apoptosis immediately after birth, the time at which the ovarian reserve is established (Grive et al, 2014).…”
Section: The Transcriptional Control Of Primordial Follicle Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the best-characterized selective subunits of the general transcriptional complex TFIID is TBP-associated factor 4b (TAF4b), a paralog of TAF4, originally identified in a human B-cell line and found to be primarily enriched in the mouse ovary and testis (Freiman et al, 2001). Taf4b-deficient female mice are viable but infertile and suffer from many hallmarks of premature ovarian failure, including follicle depletion, persistent estrous and high serum levels of the gonadotropin follicle stimulating hormone (FSH) (Falender et al, 2005;Freiman et al, 2001;Lovasco et al, 2010;Voronina et al, 2007). Recent work has demonstrated that Taf4b-deficient ovaries experience dramatic germ cell loss by apoptosis immediately after birth, the time at which the ovarian reserve is established (Grive et al, 2014).…”
Section: The Transcriptional Control Of Primordial Follicle Developmentmentioning
confidence: 99%
“…Impaired cyst breakdown; loss of primordial follicles (Lechowska et al, 2011;Rajkovic et al, 2004;Suzumori et al, 2002) TBP-associated Factor 4b (Taf4b) Impaired cyst breakdown; loss of primordial follicles (Falender et al, 2005;Freiman et al, 2001;Grive et al, 2014;Lovasco et al, 2010;Voronina et al, 2007) …”
Section: Signaling During Primordial Follicle Formationmentioning
confidence: 99%
“…In brief, they evaluated the levels of gene expression in these mice in comparison with WT controls. Interestingly, Mov10l1 was found to be expressed in mouse oocytes, and their expression levels were significantly reduced in the Taf4b-null mouse (Lovasco et al 2010). Although the Mov10l1 K/K ; mutants contained the reduced transcription levels of the MILI protein, they also lacked piRNAs binding to this protein.…”
Section: Role Of Mov10l1mentioning
confidence: 99%
“…It was recently suggested that reduced Mov10l1 levels were at least partially responsible for accelerated ovarian aging and follicle depletion in mice that lack the transcriptional regulator TAF4B (16). However, in contrast to this proposal, female Mov10l1 −/− mice appeared to have normal and sustained fertility (9 ± 1.1 pups per litter; n = 10 litters), and we assume therefore that reduced Mov10l1 expression in TAF4B −/− mice is a marker rather than a cause for accelerated ovarian aging.…”
Section: Global Deletion Of Mov10l1 Blocks Spermatogenesis During Meimentioning
confidence: 99%
“…We discovered a putative DExD-box helicase (called CHAMP; cardiac helicase activated by MEF2C protein), encoded by differently sized transcripts in heart (exons [15][16][17][18][19][20][21][22][23][24][25][26] and testis (exons 1-26) (9). The testis-specific isoform has also been referred to as MOV10-like-1 (MOV10L1), on the basis of its extensive homology to Moloney leukemia virus 10 (MOV10), which was shown to interact with argonaute 1 and 2 in HeLa cells (10).…”
mentioning
confidence: 99%